2014
DOI: 10.1002/pssc.201300453
|View full text |Cite
|
Sign up to set email alerts
|

GaN high electron mobility transistors on silicon substrates with MBE/PVD AlN seed layers

Abstract: In the present paper, we describe the development of new AlN seed layers obtained by combining molecular beam epitaxy and low temperature physical vapour deposition (magnetron sputtering). It is shown that it is possible to grow thick AlN seed layers with a good in-plane crystal ordering. GaN based structures on silicon can then be regrown with device quality active layers, as attested by the realization of high electron mobility transistors. Furthermore, the low substrate bowing achieved with these structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…22 Despite these challenges, AlN is also commonly utilized as a buffer or seed layer for the growth of GaN and III-N alloys on Si to prevent liquid Ga at the Si growth surface, facilitate elimination of threading dislocations, and enable growth of compressive GaN to counteract tensile stresses created by the large CTE mismatch between GaN and Si. 21,23 In addition to the above challenges, charge transport and carrier recombination at the AlN/Si interface are a significant consideration for the performance and reliability of AlN/Si and other III-N/Si heterostructure devices. 24,25 However, there have been relatively few investigations of the valence and conduction band alignment at III-N/Si interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…22 Despite these challenges, AlN is also commonly utilized as a buffer or seed layer for the growth of GaN and III-N alloys on Si to prevent liquid Ga at the Si growth surface, facilitate elimination of threading dislocations, and enable growth of compressive GaN to counteract tensile stresses created by the large CTE mismatch between GaN and Si. 21,23 In addition to the above challenges, charge transport and carrier recombination at the AlN/Si interface are a significant consideration for the performance and reliability of AlN/Si and other III-N/Si heterostructure devices. 24,25 However, there have been relatively few investigations of the valence and conduction band alignment at III-N/Si interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Cordier et al [51] performed MBE growth of 1-1.5 μm thick GaN on Si (111) through AlN buffer layers deposited by dc magnetron sputtering at substrate temperatures below 200 °C. The AlN films were composed of nanocolumns of 20-30 nm diameter with a preferential c-axis orientation in the growth direction, but without any noticeable in-plane ordering.…”
Section: Sputtered Aln Buffers For Growth On Si Substratesmentioning
confidence: 99%
“…As discussed above, the AlN nucleation layers deposited by low-temperature sputtering can effectively reduce the density of threading dislocations that act as non-radiative recombination centers and carrier leakage paths, thus deteriorating efficiency of GaN-based optoelectronic devices. The sputtered AlN buffers were found to be effective for improving characteristics of various GaN-based electronic and optoelectronic devices, including LEDs [12][13][14][15][16][17][18][19][20][30][31][32], metalsemiconductor-metal (MSM) UV photodetectors [38], solar cells [34], and FETs [51]. Many groups reported that improved light output power (LOP) can be achieved due to lower TD density in GaN-based LED structures grown on sputtered AlN buffers [12][13][14][15][16][17][18][19][20]31].…”
Section: Device Applications Of Iii-nitrides Grown On Sputtered Aln B...mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, aluminum nitride has been of particular interest since it is a large band gap material that is desirable for its high resistivity and piezoelectric coupling coefficient. 92 AlN can be deposited by several methods such as molecular beam epitaxy (MBE) and physical vapor deposition (PVD), 93 but neither of these techniques allows for the precise thickness and conformality control of ALD.…”
Section: Introductionmentioning
confidence: 99%